2012
DOI: 10.1158/0008-5472.can-11-4149
|View full text |Cite
|
Sign up to set email alerts
|

Novel MT1-MMP Small-Molecule Inhibitors Based on Insights into Hemopexin Domain Function in Tumor Growth

Abstract: Membrane type-1 matrix metalloproteinase (MT1-MMP) is a promising drug target in malignancy. The structure of MT1-MMP includes the hemopexin domain (PEX) that is distinct from and additional to the catalytic domain. Current MMP inhibitors target the conserved active site in the catalytic domain and, as a result, repress the proteolytic activity of multiple MMPs instead of MT1-MMP alone. In our search for non-catalytic inhibitors of MT1-MMP, we compared the pro-tumorigenic activity of wild-type MT1-MMP with a M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
109
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 42 publications
4
109
0
Order By: Relevance
“…Accordingly, preclinical proof of principle rationale was recently provided for the design and development of novel and selective MT1-MMP inhibitors that specifically target its hemopexin domain (42), whereas recent molecular profiling has identified actinonin, originally classified as an aminopeptidase N/CD13 pharmacological inhibitor, with MT1-MMP targeting functions (43). Finally, impact on lymphangiogenesis with selective targeting of MT1-MMP was also achieved through the use of specific monoclonal antibodies (44), whereas AG3340, a potent small molecule MT1-MMP antagonist, was required for the design of novel therapies for type 1 diabetes (45).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, preclinical proof of principle rationale was recently provided for the design and development of novel and selective MT1-MMP inhibitors that specifically target its hemopexin domain (42), whereas recent molecular profiling has identified actinonin, originally classified as an aminopeptidase N/CD13 pharmacological inhibitor, with MT1-MMP targeting functions (43). Finally, impact on lymphangiogenesis with selective targeting of MT1-MMP was also achieved through the use of specific monoclonal antibodies (44), whereas AG3340, a potent small molecule MT1-MMP antagonist, was required for the design of novel therapies for type 1 diabetes (45).…”
Section: Discussionmentioning
confidence: 99%
“…Gelatin Zymography and Western Blotting-Gelatin zymography of the conditioned medium aliquots and Western blotting of the cell lysate samples were performed as described earlier (65,66). For gelatin zymography, where indicated, the purified MMP-2 proenzyme (0.5 nM) was added to the cells.…”
Section: Methodsmentioning
confidence: 99%
“…In both in vitro and in vivo systems, designed small molecules and peptides exert their inhibitory effects by preventing dimerization, thereby reducing tumor size, MMP-induced migration, and angiogenesis. [158][159][160] Promising studies have shown that these selective compounds could bind on specific sites for each MMP inside their hemopexin domain and prevent dimer-induced functions of several MMPs, including MMP14 and -9. [158][159][160][161][162] A more sophisticated approach proposed a bifunctional fusion protein able to bind and inactivate both the catalytic and hemopexin domains of MMP2.…”
Section: Targeting the Mmp Noncatalytic Domainmentioning
confidence: 99%